Translating hierarchy in Hideo Yokoyama’s The Third Deadline - Sundin, Lola; Tobias, Shani (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2022)
Crime fiction is a genre that commonly incorporates important sociocultural dimensions. When crime fiction works are translated within the framework of world literature, new audiences are able to expand their knowledge of different cultures and societies, as well as be entertained by the plots and characters. It can thus be a challenge, for translators, to ensure that sociocultural aspects are effectively conveyed. For example, the translation into English of Japanese social and organisational hierarchy depicted in character interactions is particularly complex, given the differing linguistic and cultural backgrounds of readers. This paper explores strategies for translating hierarchy using Hideo Yokoyama’s Dai san no jikō (The Third Deadline) as a case study. We propose a methodology to assist translators in adopting a conscious approach to translating hierarchy, which will provide readers with a more nuanced understanding of how hierarchy functions in Japanese society. We demonstrate that the translation of crime fiction can help readers overcome barriers resulting from linguistic and cultural differences to gain a new understanding of different societies.